2016
DOI: 10.18203/2349-3933.ijam20162495
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder: a short review

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common childhood psychiatric disorder with a prevalence of 4 to 8%. ADHD is characterized by hyperactivity, impulsiveness, and inappropriate inattentiveness. Though long considered a disease of childhood, studies have shown that a majority of cases persist in adulthood causing significant psychosocial impairment. Diagnosis is often based on clinical symptoms, and psychostimulants are mainstay in treatment of ADHD that are often complemented by psychotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…However, drug treatments alone have not achieved sufficient success in reducing problem behaviors (Evans et al, 2008). It has been concluded that combining psychotherapy, behavioral therapy and psychoeducational support with drug therapy will yield more positive results when treating ADHD (Gill & Bhatt, 2016;Elsayed & Salama, 2020;Hafeez, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, drug treatments alone have not achieved sufficient success in reducing problem behaviors (Evans et al, 2008). It has been concluded that combining psychotherapy, behavioral therapy and psychoeducational support with drug therapy will yield more positive results when treating ADHD (Gill & Bhatt, 2016;Elsayed & Salama, 2020;Hafeez, 2022).…”
Section: Introductionmentioning
confidence: 99%